Increasing Access to Electricity in the Democratic Republic of Congo : Opportunities and Challenges - World Bank (World Bank, Washington, DC, 2020)
The main priority for the Democratic Republic of Congo’s power sector is to increase access to electricity. The Democratic Republic of Congo is a large country with 10 million households of which 1.6 million have access to electricity. This makes it the third largest population in the world without access to electricity. The report explores the current state of the electricity sector in the DRC, including opportunities and challenges, and presents a set of recommendations, focusing on principles and priorities to proceed with future power sector development. It defines how these principles can be implemented in planning the sector development and identifies some of the investments required to move towards the goal of universal access to electricity. The note could contribute to the definition of a short and medium-term roadmap for the government and for donors.